A review: training requirement of agriculture extension officers in Iraq - Saleh, Jasim Mohammed; Man, Norsida; Lafta, Ahmad Hamdan; Saleh, Majeed Hadi; Hassan, Salim; Mohd Nawi, Nolila; Kshash, Bassim Haleem (Knowledgia Review, Malaysia, 2016)
The training of agricultural extension workers is an integral part of the overall agricultural production process. It is the duty of agricultural extension agents to reach farmers scattered around the country with useful and practical information for increased agricultural production. In-service training of the extension agents is the call of the time. Training needs were assessed using the Borich Needs Assessment Model. This Model is designed around the skills individuals and groups need to be effective in the future and are used for making human resources decisions. Through trained agricultural extension agents new agricultural technology can easily and favorably be transferred to clientele. Training should not be conducted at the time of sowing and harvesting time and lectures should be carried out during the training sessions and choose time suitable for agricultural extension workers. Thus, necessary steps should be taken to identify the unfelt needs of the agricultural extension workers and strengthen their knowledge, skills and attitudes required for performing their job efficiently.